2017
DOI: 10.1136/gutjnl-2016-312888
|View full text |Cite
|
Sign up to set email alerts
|

Epidermal growth factor receptor inhibition downregulatesHelicobacter pylori-induced epithelial inflammatory responses, DNA damage and gastric carcinogenesis

Abstract: Objective Gastric cancer is the third leading cause of cancer death worldwide and infection by Helicobacter pylori is the strongest risk factor. We have reported increased epidermal growth factor receptor (EGFR) phosphorylation in the H. pylori-induced human carcinogenesis cascade, and association with DNA damage. Our goal was to determine the role of EGFR activation in gastric carcinogenesis. Design We evaluated gefitinib, a specific EGFR inhibitor, in chemoprevention of H. pylori-induced gastric inflammati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
60
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(62 citation statements)
references
References 55 publications
1
60
1
Order By: Relevance
“…18 This year, the Wilson group also showed that treatment of H. pylori-infected INS-GAS mice or Mongolian gerbils with the EGFR inhibitor gefitinib resulted in (a) reduced activation of MAPK1/3 and activator protein 1 in GECs, (b) inhibition of chemokine synthesis by the gastric mucosa, (c) a decrease in myeloperoxidase-positive inflammatory cells, and (d) a marked reduction of gastric dysplasia and carcinoma. 19 Of particular interest, similar data were obtained in mice with epithelial cell-specific deletion of Egfr (Egfr Δepi ) and key findings were recapitulated using culture of primary GEC monolayers of WT and Egfr Δepi mice. Altogether, these data prove that the recruitment of myeloperoxidase-positive inflammatory cells to the infected gastric mucosa is orchestrated by epithelial EGFR.…”
Section: Regulation Of Inflammation By Cellular Receptorsmentioning
confidence: 71%
“…18 This year, the Wilson group also showed that treatment of H. pylori-infected INS-GAS mice or Mongolian gerbils with the EGFR inhibitor gefitinib resulted in (a) reduced activation of MAPK1/3 and activator protein 1 in GECs, (b) inhibition of chemokine synthesis by the gastric mucosa, (c) a decrease in myeloperoxidase-positive inflammatory cells, and (d) a marked reduction of gastric dysplasia and carcinoma. 19 Of particular interest, similar data were obtained in mice with epithelial cell-specific deletion of Egfr (Egfr Δepi ) and key findings were recapitulated using culture of primary GEC monolayers of WT and Egfr Δepi mice. Altogether, these data prove that the recruitment of myeloperoxidase-positive inflammatory cells to the infected gastric mucosa is orchestrated by epithelial EGFR.…”
Section: Regulation Of Inflammation By Cellular Receptorsmentioning
confidence: 71%
“…showed that gefitinib, a specific EGFR inhibitor, was able to decrease the epithelial DNA damage induced by H. pylori infection in C57BL/6 mice. Furthermore, it blocked H. pylori ‐induced activation of MAPK1/3 and AP‐1 in gastric epithelial cells and markedly reduced dysplasia and carcinoma in infected INS‐GAS mice and gerbils . This suggests that in H. pylori ‐infected individuals, epithelial EGFR blockage may represent a putative cancer preventive strategy.…”
Section: Deregulation Of Host Functionsmentioning
confidence: 88%
“…Previous study demonstrated that the CagA of H pylori activated various intracellular signaling pathways, including the NF‐κB pathway and MAP kinases via EGFR activation . In vitro, Sierra et al showed that a specific EGFR inhibitor was able to decrease the epithelial DNA damage induced by H pylori infection. It can be seen that EGFR plays a key role in the process of H pylori infection.…”
Section: Discussionmentioning
confidence: 99%